Clonagem e expressão heteróloga de proteínas estruturais (C, prM, E) de Zika Virus (ZIKV) - Bonomo, Jéssica Hilário (2018)
Viruses are organisms which depend on the host cellular machinery to replicate, and are relevant to human, livestock and plant health. The modern threat of emerging pandemics is pressing and, in this scenario, Zika Virus (ZIKV) is an important recent example, due to recent epidemics and confirmation of its involvement in congenital development and neurological manifestations. The ability to produce recombinant virus like particles (VLPs) and recombinant proteins can lead to the understanding of its structure and the development of new therapeutic approaches, as well as the understanding of interaction mechanisms between the virion and host cell. This study aims to achieve heterologous production of ZIKV VLPs as well as ZIKV Capsid protein for future structural analysis and to make them available to the research community. A recombinant construct containing the three structural proteins of ZIKV (C, prM and E) cloned into pPICZα vector was integrated in Pichia pastoris genome for AOX1 promoter induced expression. C protein coding region was cloned into Escherichia coli expression vector for separate expression and purification by affinity chromatography using a 6xHis tag construct. Integration of the coding region for the proteins C, prM and E in the P. pastoris genome was confirmed via PCR and sequencing. Results showed the possibility of obtaining soluble secreted recombinant product. Production of isolated C protein was achieved in E. coli and its purification was performed through affinity chromatography.